Determination of Optimum Operating Frequencies for Observations with UTR-2 Radio Telescope in the Sky Surveying Mode - Konovalenko, O. O.; Sokolov, K. P.; Stepkin, S. V. (Видавничий дім «Академперіодика», 2013)
Determination of Optimum Operating Frequencies for Observations with UTR-2 Radio Telescope in the Sky Surveying Mode